Maitasine - Abdul Rahman I. Doi (International Institute of Islamic Thought, 1987)
There have been errorneous statements made by some writers that the "Izalah Muslim sect, which is officially recognized, has a doctrine similar to those of Muhammadu Marwa Maitatsine". This was the interpretation of West Africa Magazine and also that of Dr. M. A. Ojo whose article on The Maitatsine Revolution in Nigeria appeared in the American Journal Islamic Social Sciences. The actual name of Izalah Movement is Izalat al-Bid'ah Wa Iqamat al- Sunnah, the movement that aims at removing devilic innovations (al-Bid'ah al-Shaytaniyyah) and establishing Sunnah in the life of Muslims on the same pattern as that of the great Nigerian Mujahid and Mujaddid Shaikh 'Uthman Danfodio. The person who started this reform movement is no other than Shaikh Abubakar Mahud Gumi who has been recently recognized and awarded King Faysal Award for his meritorious services to the cause of Islam in Africa. The question is then, who was Maitatsine or who are the Maitatsine followers who made their very strange appearance in Nigeria at dijerent times? I have read all the writings about Maitatsine by various scholars and I have closely tried to study this mischievous anti-Islamic and destructive movement, but as time goes on I have become more and more perplexed like many of my friends about the real identity of Maitatsine and his followers. The recent write-up by the columnist Candido in New Nigerian Newspaper entitled, "The Maitatine Scare", on Wednesday April 8,1987 is an alarming disclosure: ...